2000
DOI: 10.1073/pnas.080508097
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of palmitoyl protein thioesterase 1 and the molecular basis of infantile neuronal ceroid lipofuscinosis

Abstract: Mutations in palmitoyl-protein thioesterase 1 (PPT1), a lysosomal enzyme that removes fatty acyl groups from cysteine residues in modified proteins, cause the fatal inherited neurodegenerative disorder infantile neuronal ceroid lipofuscinosis. The accumulation of undigested substrates leads to the formation of neuronal storage bodies that are associated with the clinical symptoms. Less severe forms of PPT1 deficiency have been found recently that are caused by a distinct set of PPT1 mutations, some of which re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
128
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 143 publications
(131 citation statements)
references
References 41 publications
3
128
0
Order By: Relevance
“…4. The position of the palmitate residue corresponds to the position observed in the crystal structure of PPT1 (for review, see "Results and Discussion") (10). b, fatty acid specificity of PPT1 and -2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…4. The position of the palmitate residue corresponds to the position observed in the crystal structure of PPT1 (for review, see "Results and Discussion") (10). b, fatty acid specificity of PPT1 and -2.…”
Section: Resultsmentioning
confidence: 99%
“…By 10 months of age, most PPT1 knockout mice are dead, whereas mortality in the PPT2 knockout mice is only 20%; however, most mice show spasticity by that age. The crystal structure of PPT1 alone and in complex with palmitate solved in our laboratory (10) showed that PPT1 has an ␣-␤ hydrolase fold with an additional lipid binding domain. This information provided the structural basis for understanding the severity of phenotypes associated with different PPT1 mutations.…”
Section: Neuronal Ceroid Lipofuscinosis (Ncl)mentioning
confidence: 99%
“…The reported finding that inhibition of protein synthesis by DB in MCF-7 human breast carcinoma cells occurs at concentrations that are about 1 order of magnitude lower than those required for induction of apoptosis via caspase activation has been taken as evidence for a second mechanism of action and/or a second target protein. 44 PPT-1 has apparently failed to fulfill the role of a secondary pharmacological target, 8 and no obvious structural similarity is apparent between this enzyme 45 and eEF1A beyond the common R/ hydrolase fold. For this reason, it might be worth taking into account that, apart from being an essential partner in the mechanism of translational elongation, eEF1 is considered to be an important multifunctional (moonlighting) protein 46 whose levels are positively correlated with the proliferative state of cells.…”
Section: Discussionmentioning
confidence: 99%
“…We wondered whether there might be structural and/or mechanistic differences between PPT1 and these other lipolytic enzymes that would account for this observation. We have recently determined the three-dimensional crystal structure of PPT1 in the presence and absence of palmitoyl-CoA and shown that palmitate modifies serine 115 of the enzyme (5), confirming that a serine residue is the catalytic nucleophile.…”
mentioning
confidence: 99%